Faktor-Faktor yang Mempengaruhi Pendapatan Usaha Pedagang Bakso di Kecamatan Meureubo Kabupaten Aceh Barat - Ramadhan, Aiyub Fadhilla; Sani, Sri Rosmiati; Manan, Afni Abdul (Riwayat: Educational Journal of History and Humanities, 2025)
Meatball trading is a popular business choice due to high consumer demand, providing an opportunity for individuals to improve their income and economic welfare, particularly in Meureubo District, West Aceh Regency. This study aims to analyze the effect of capital, business duration, number of workers, and selling price on the income of meatball traders in the area. The research applies a quantitative approach involving 12 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The findings indicate that during the research period in July 2024, the total income of meatball traders reached IDR 58,980,000, calculated from total revenue of IDR 133,800,000 minus total costs of IDR 74,820,000. The statistical results demonstrate that capital, business duration, number of workers, and selling price simultaneously have a significant and positive effect on trader income, with the model explaining 91.1% of the income variation, while the remaining 8.9% is influenced by other factors outside the model. Furthermore, partial analysis reveals that capital, business duration, and selling price significantly and positively affect income, whereas the number of workers does not show a significant individual effect. These results highlight the importance of capital investment, operational experience, and pricing strategy in enhancing traders' income.